Eucalyptus Plantation Age and Species Govern Soil Fungal Community Structure and Function Under a Tropical Monsoon Climate in China - Liu, Bing; Qu, Zhaolei; Ma, Yang; Xu, Jie; Chen, Pei; Sun, Hui (Frontiers in Fungal Biology, 2021)
Fungi perform crucial roles in nutrient cycles, but there is limited information on how soil fungal communities vary with stand age and tree species. Eucalyptus has been extensively planted in China, which has caused severe soil erosion and water deficiency due to the short rotation management. In the present study, the fungal community structure and potential function in Eucalyptus plantations with different ages (1–5+ years) and species (E. urophylla×E. grandis, E. camaldulens, and E. pellita) under a tropical monsoon climate in China were characterized by Illumina Miseq coupled with FUNGuild analysis. The results showed that the fungal alpha-diversity decreased with an increase in the plantation’s age. Plantations of different ages and species formed distinct fungal communities and potential functional structures, respectively (p < 0.05), in which the plantation’s age contributed more to the variations. At high taxonomic levels, the soil fungal community changed from the dominance of orders belonging to Ascomycota (Pleosporales, Chaetothyriales, and Eurotiales) to orders belonging to Basidiomycota (Agaricales, Sebacinales, Cantharellales, and Russulales) with increasing plantation age. The community potential function shifted from the dominance of plant pathogens to a higher abundance of saprotrophs and symbiotrophs. The soil organic carbon was the key environmental driver to both fungal community and potential functional structure. The results provide useful information on the importance of fungi for the management of Eucalyptus plantations